Experimental investigation and optimizationfor the effective parameters in the laser direct structuringprocess - Bachy, Bassim; Franke, Jörg (Journal of Laser Micro Nanoengineering, 2015)
The laser direct structuring (LDS) and the molded interconnect devices (MID) processes become more popular in the electronics industry. In order to produce micro MID products with highest circuit lines quality, it is very important to understand the complex relationship among the laser direct structuring parameters, the dimensions of the groove at the substrate surface, the profile of this groove, the width of the interactive zone (circuit line width) and space between two circuit lines (pitch). To reveal this relationship, experiments on the polymer plate (polyphthalamide PPA, with glass fiber) have been carried out in this work. It was found that the effect of the laser speed and laser power on the groove profile and dimensions are greater than the effect of the laser frequency, moreover the metallization profile depends on the groove profile which again depends on the LDS parameters. The dimensions of the resolidification groove edge including the width and height must be reduced to lowest possible value, in order to reduce the metallization defects.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Laser direct structuring process; Laser process; Microstructure; Molded interconnected devices process